Children's exposure to phthalates and non-phthalate plasticizers in the home: The TESIE study. (November 2019) - Hammel, Stephanie C.; Levasseur, Jessica L.; Hoffman, Kate; Phillips, Allison L.; Lorenzo, Amelia M.; Calafat, Antonia M.; Webster, Thomas F.; Stapleton, Heather M.
Abstract: Background: Phthalates and their potential replacements, including non-phthalate plasticizers, are ubiquitous in home environments due to their presence in building materials, plastics, and personal care products. As a result, exposure to these compounds is universal. However, the primary pathways of exposure and understanding which products in the home are associated most strongly with particular exposures are unclear. Objectives: We sought to investigate the relationships between phthalates and non-phthalate plasticizers in paired samples of house dust, hand wipes, and their corresponding metabolites in children's urine samples (n = 180). In addition, we compared product use or presence of materials in the household against all compounds to investigate the relationship between product use or presence and exposure. Methods: Children aged 3–6 years provided hand wipe and urine samples. Questionnaires were completed by mothers or legal guardians to capture product use and housing characteristics, and house dust samples were collected from the main living area during home visits. Results: Phthalates and non-phthalate replacements were detected frequently in the environmental matrices. All urine samples had at least 13 of 19 phthalate or non-phthalate replacement metabolites present. Hand wipe mass and dust concentrations of diisobutyl phthalate, benzyl butyl phthalate (BBP), bis(2-ethylhexyl) phthalate, and di-isononyl phthalate were significantly associated with their corresponding urinary metabolites (rs  = 0.18–0.56, p < 0.05). Bis(2-ethylhexyl) terephthalate (DEHTP) in dust was also significantly and positively correlated with its urinary metabolites (rs  = 0.33, p < 0.001). Vinyl flooring was most significantly and positively associated with particular phthalate exposures (indicated by concentrations in environmental matrices and urinary biomarkers). In particular, children who lived in homes with 100% vinyl flooring had urinary concentrations of monobenzyl phthalate, a BBP metabolite, that were 15 times higher than those of children who lived in homes with no vinyl flooring (p < 0.0001). Levels of BBP in hand wipes and dust were 3.5 and 4.5 times higher, respectively, in those homes with 100% vinyl flooring (p < 0.0001 for both). Conclusions: This paper summarizes one of the most comprehensive phthalate and non-phthalate plasticizer investigation of potential residential exposure sources conducted in North America to date. The data presented herein provide evidence that dermal contact and hand-to-mouth behaviors are important sources of exposure to phthalates and non-phthalate plasticizers. In addition, the percentage of vinyl flooring is an important consideration when examining residential exposures to these compounds. Highlights: Plasticizers were frequently detected in children's hand wipes, dust, and urine. Phthalates in hand wipes and house dust were correlated with metabolites in urine. The metabolite of BBP was higher in children who lived in homes with 100% vinyl floors. DEHTP was more abundant than DEHP in house dust and child hand wipes.